Pengembangan wawasan nusantara dan implementasi nilai-nilai pancasila pada generasi Z - Komariyah, Aliyah Nur (Maliki Interdisciplinary Journal, 2025)
The principles of Archipelagic Insight and Pancasila serve as vital pillars in preserving Indonesia’s unity amid its rich cultural diversity. Nevertheless, the younger generation, especially Generation Z who are growing up immersed in the digital era, encounter notable obstacles in comprehending and embracing these national values. Constant exposure to global information and foreign cultures via social media, combined with rapid technological advancements, can lead to identity confusion and diminishing national pride if not addressed properly. This study explores effective methods to instill Archipelagic Insight and Pancasila values within Generation Z. Utilizing a library research approach, it analyzes a range of scholarly literature, including journals, books, and policy documents. The study finds that fostering national consciousness among Generation Z demands tailored approaches compatible with their digital habits. Recommended strategies involve embedding national values within university curricula, leveraging social media platforms for educational purposes, and promoting active participation from families and educational institutions in character development. Additionally, enhancing ideological literacy is essential to ensure that Pancasila principles are not merely theoretical concepts but are applied in everyday behavior. The study advocates for coordinated efforts among various stakeholders to establish a supportive ecosystem that nurtures the national identity and character of Indonesia's future generations.